The classification of concentration of mixture of analytes using total principal component regression - Baronas, Romas; Ivanauskas, Feliksas; Paulauskas, Robertas; Vaitkus, Pranas (Lietuvos matematikos rinkinys, 2005)
In this paper total principal component regression is used for biosensors response to mixtures of compounds classification. The results are compared with the results obtained using artificial neural networks.
Keywords: total principal component regression; pseudo inversematrix